E-Module Statistics Based on Tajweed in Al-Kahf and Interest in Reading Quran : E-Modul Statistika Berbasis Ilmu Tajwid dalam Al-Kahfi dan Minat Baca Quran - Khasanah, Binti Anisaul; Astuti, Robia; Nurmitasari, Nurmitasari (Halaqa: Islamic Education Journal, 2025)
The obligation to read the Qur'an in accordance with the rules of the Tajwid science makes the knowledge of Tajwid very important to be studied by every Muslim, not except by the students who are Muslims. On the other hand, learning Tajwid science for students at school can be integrated with other subjects, including mathematics. Therefore, this study aims to demonstrate the effectiveness of the e-statistical module integrated in the science of tajwid in the Al-Kahfi letter reviewed from the interest of reading the Quran of Muhammadiyah high school students of Pringsewu district. The type of research used is a quasi-experiment with a 2x3 factorial design. The population in this study is the entire high school student Muhammadiyah of the Pringsewu district with the technique of sampling using random sample clusters. Research data is collected through the lifting and testing methods, while data analysis techniques use two-way analysis. The results of this study show that the use of e-statistical modules integrated tajwid science in Al-Kahfi letters is effectively used in learning both for students who have an interest in reading Al-Qur'an high, medium, or low.Highlights: Integrated Learning: Combining Tajwid with statistics enhances both religious and mathematical education. Effective E-Module: The digital module significantly improves students' learning outcomes in statistics. Reading Interest Impact: Higher Quran reading interest correlates with better academic performance. Keywords: E-Modul, Tajwid Science, Statistics, Al-Kahfi, Interest in Reading Al-Quran